Gut microbiota and brain aging: a comparative review of African and western populations - Ortutu, Beulah Favour; Okin, Abidemi Oluwasanmi; Darkwah, Kwame Osei; Onuorah, Uju Maryanne; Maigoro, Abdulkadir Yusif; Iheme, Gideon Onyedikachi (Frontiers in Aging Neuroscience, 2026)
As the population ages, cognitive decline and neurodegenerative diseases have become major public health concerns. The human gut microbiota plays a major role in regulating neurodevelopment, neuroinflammation, and cognitive decline through the gut-brain axis. Emerging evidence reveals a possible association between alterations in gut microbial diversity and age-related neurological disorders, including Alzheimer’s disease and neurodegeneration. Regional and dietary differences shape the gut microbiome. These variations may, in turn, be associated with differences in brain aging across populations. Several cross-sectional studies indicate that rural African communities consuming predominantly fiber-rich diets exhibit distinct gut microbiota profiles characterized by increased abundance of genera, including Prevotella, Faecalibacterium, and Ruminococcus. These microbial configurations have been associated with improved gut barrier integrity, reduced systemic inflammation, and enhanced production of short-chain fatty acids in some preclinical and human studies. All these factors have been studied as potential mechanisms linked to delayed brain aging. Furthermore, epidemiological reports suggest lower prevalence rates of dementia and other neurodegenerative disorders in these populations, although such comparisons may be influenced by differences in study design, diagnosis, and case ascertainment across regions. This narrative review synthesized current understanding of the gut microbiota’s role in brain aging, summarized available data on gut microbiota composition in African versus Western populations, and explored the pathways by which traditional African diets may contribute to neuroprotection. By critically examining this evidence and highlighting major research gaps, the review advocates for region-specific investigations and future longitudinal studies to validate causal links.